2014
DOI: 10.1021/ie402563j
|View full text |Cite
|
Sign up to set email alerts
|

MINLP Formulation for Simultaneous Planning, Scheduling, and Control of Short-Period Single-Unit Processing Systems

Abstract: A simultaneous strategy for solving the integrated planning, scheduling and control problem considering short-term periods is proposed in this paper. The problem is formulated as a mixed integer dynamic optimization problem. The main practical motivation to use a simultaneous, rather than a sequential solution strategy is to seek improved optimal solutions by considering the interactions among planning, scheduling and control. Integration of the three levels of the problem represents a challenge given the very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Literature on ISC reactive to market fluctuations is relatively limited in scope. Gutierrez-Limon et al demonstrated integrated planning, scheduling, and control responsive to fluctuations in market demand on a CSTR benchmark application [36,37]. Pattison et al investigated ISC with an air separation unit (ASU) in fast-changing electricity markets, responding optimally to price fluctuations [42].…”
Section: Responsiveness To Market Fluctuationsmentioning
confidence: 99%
“…Literature on ISC reactive to market fluctuations is relatively limited in scope. Gutierrez-Limon et al demonstrated integrated planning, scheduling, and control responsive to fluctuations in market demand on a CSTR benchmark application [36,37]. Pattison et al investigated ISC with an air separation unit (ASU) in fast-changing electricity markets, responding optimally to price fluctuations [42].…”
Section: Responsiveness To Market Fluctuationsmentioning
confidence: 99%
“…Benefit is demonstrated from using multi-objective approaches with Pareto fronts rather than combining economic and dynamic performance objectives into a single objective function. Gutierrez-Limon and Flores-Tlacuahuac also investigate simultaneous planning, scheduling, and control for continuous chemical processes using a large MINLP problem and NMPC [41]. Prata et al study the use of outer approximation methods for the solution of integrated scheduling and control problems [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[70,119] Simultaneous/Decomposition (MI)DO schedule and P-PI-PID control [58,93,225,269] Simultaneous/Decomposition algorithms using control/dynamics aware scheduling models [42,122,370] Simultaneous/Decomposition algorithms via (MI)DO reformulation to (MI)NLP [161,183,184,277,335,336] Control theory in scheduling problems [146,147,277,362] Advanced control and (MI)NLP scheduling schemes [75,158,166,204,270] Scheduling under uncertainty [19,29,102,126,142,153] Review articles on scheduling and control and methodologies…”
Section: Introductionmentioning
confidence: 99%